2008
DOI: 10.1111/j.1479-828x.2008.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal radiofrequency thermal ablation: A day‐care approach to symptomatic uterine myomas

Abstract: The results of this study suggest that RF ablation may represent a safe, well-tolerated, and effective day-care alternative to conventional surgery for the treatment of uterine myomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 16 publications
3
30
0
3
Order By: Relevance
“…It has been shown that radiofrequency ablation results in heat/ thermal fixation and coagulative necrosis within the treated fibroids [9,10]. Recent studies have been performed using RFA in conjunction with simultaneous, real-time sonography to enable volumetric ablations that result in volume reduction and symptomatic relief [8,9,11].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been shown that radiofrequency ablation results in heat/ thermal fixation and coagulative necrosis within the treated fibroids [9,10]. Recent studies have been performed using RFA in conjunction with simultaneous, real-time sonography to enable volumetric ablations that result in volume reduction and symptomatic relief [8,9,11].…”
Section: Introductionmentioning
confidence: 98%
“…Cho and colleagues performed transcervical fibroid RFA in 153 women who were followed up to 18 months posttreatment [8]. Symptomatic relief was assessed through the Uterine Fibroid Symptom-Quality of Life questionnaire; the authors reported a 91% reduction in symptoms and a 46% improvement in quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La myolyse par radiofréquence peut être guidée par coelioscopie ou par échographie [16][17][18][20][21][22]. Une large zone de nécrose (supérieure à 6 cm de diamètre) peut être obtenue par un abord unique et donc comparée à la cryothérapie, c'est une technique moins consommatrice de temps.…”
Section: La Myolyse Par Radiofréquenceunclassified
“…Ces techniques ont été évaluées dans le traitement des myomes sous-muqueux, seules, en association à la myomectomie par résection hystéroscopique (Tableau 2) ou plus rarement en association à des techniques de myolyse par voie vaginale (Tableau 3) [2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Indicationsunclassified